English use at the six social service centers in Reykjavík: English as the lingua Franca of social services in Reykjavik - Barbara Jean Kristvinsson 1958- (2012)
English has become a global language and the number of users of English who are not native speakers has exceeded the numbers of native speakers. While studies show that Scandinavians are proficient users of English very little is known about how much English the average Icelander encounters on a daily basis. English has become a lingua franca in many companies and private and public institutions in Iceland where it may primarily be used among non-native speakers. Previous research done at the University of Iceland suggests that Icelandic users of English may overestimate their English proficiency, and as exposure to English is largely confined to reading and listening, proficiency may be much higher in receptive language skills than productive skills causing difficulty when professionals are called to use English in communication. Research is being done on Icelandic companies and institutions and this thesis examines the six social service centers in Reykjavik. The role of these centers is to inform, assist and serve all those living in Reykjavik. Can the staff speak, read and write English as the demands of their job dictate? How do they view their own proficiency and how often do they actually use English? To answer these questions, an electronic survey was sent to the 198 employees currently working for the Reykjavik Division of Welfare and located at the six social service centers scattered around Reykjavik. The results were similar to the results of previous studies in Iceland as the respondents over-estimated their English proficiency since their usage is mostly receptive and they do not actually produce English on a daily basis.